Respuesta :
Answer:
[tex]a=0.5418\ m.s^{-2}[/tex] upwards
[tex]a=1.283\ m.s^{-2}[/tex] downwards
Explanation:
Given:
weight of the person, [tex]w=688\ N[/tex]
So, the mass of the person:
[tex]m=\frac{w}{g}[/tex]
[tex]m=\frac{688}{9.81}[/tex]
[tex]m=70.132\ kg[/tex]
- Now if the apparent weight in the elevator, [tex]w_a= 726\ N[/tex]
Then the difference between the two weights is :
[tex]\Delta w=w_a-w[/tex]
[tex]\Delta w=726-688[/tex]
[tex]\Delta w=38\ N[/tex] is the force that acts on the body which generates the acceleration.
Now the corresponding acceleration:
[tex]a=\frac{\Delta w}{m}[/tex]
[tex]a=\frac{38}{70.132}[/tex]
[tex]a=0.5418\ m.s^{-2}[/tex] upwards, because the normal reaction that due to the weight of the body is increased here.
- Now if the apparent weight in the elevator, [tex]w_a= 598\ N[/tex]
Then the difference between the two weights is :
[tex]\Delta w=w-w_a[/tex]
[tex]\Delta w=688-598[/tex]
[tex]\Delta w=90\ N[/tex] is the force that acts on the body which generates the acceleration.
Now the corresponding acceleration:
[tex]a=\frac{\Delta w}{m}[/tex]
[tex]a=\frac{90}{70.132}[/tex]
[tex]a=1.283\ m.s^{-2}[/tex] downwards, because the normal reaction that due to the weight of the body is decreased here.
Answer with Explanation:
We are given that
Weight of person=w=688 N
a.Scale reading=n=726 N
[tex]m=\frac{w}{g}=\frac{688}{9.8} m[/tex]
By using [tex]g=9.8m/s^2[/tex]
Net force=ma=n-w
[tex]a=\frac{n-w}{m}=\frac{726-688}{\frac{688}{9.8}}m/s^2[/tex]
[tex]a=0.54 m/s^2[/tex]
The sign of acceleration(a) is positive.Therefore, the direction of elevator's accelerating is upwards.
b.Scale reading=n=598 N
[tex]a=\frac{598-688}{\frac{688}{9.8}}=-1.28m/s^2[/tex]
[tex]a=-1.28 m/s^2[/tex]
The sign of acceleration(a) is negative.Therefore, the direction of elevator's accelerating is downwards.